The Anatomical Architecture of the Junction between the Great Cerebral Vein and the Straight Sinus in Correlation to the Physiological and Biochemical Impact on Multiple Sclerosis Subtypes and Disease Progression (A Review Article) - WJ, Cobb; ST, Cook; MA, Gardenhire; JC, Harrington (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2016)
Multiple Sclerosis (MS) is a debilitating autoimmune disorder, characterized by damage to thewhite matter of the central nervous system. Studies suggest a relationship between impairedcerebral venous blood flow and progressive destruction of white matter in the CNS. Alteredcerebral venous architecture is a possible mechanism that may contribute to a compromisedvenous blood flow pattern in MS patients. Natural variations at junction located between thegreat cerebral vein (GCV) and the straight sinus (Ss) located within the cerebral venous drainagesystem can potentially exacerbate MS progression. Recent data indicates that abnormal cerebralvenous hemodynamics contributes to the pathophysiology observed in MS through an unknownmechanism that increases hydraulic resistance.